(untitled) (Ameghiniana, 2014)
Lanipustula patagoniensis sp. nov. is described from the Upper Palaeozoic of the Tepuel-Genoa basin in Chubut, being the first record of Lanipustula Klets in South America. The studied material was found in two different associations: one of them late Carboniferous in age and the other one probably early Permian.